Antibacterial Effect of Hypochlorous Acid on Bacteria Associated with the Formation of Periodontal Biofilms: An in vitro Pilot Study - Pablo Alejandro Millones-Gómez; Marcos Novoa-Herrera; Dora Jesús Maurtua-Torres; Reyma Evelyn Bacilio-Amaranto; Margarita Fe Requena-Mendizábal; Roger Calla-Poma; Tania Valentina Rosales-Cifuentes; Federico Martin Malpartida-Quispe; Carlos Alberto Minchón-Medina; Julio César Romero-Gamboa; Melissa Pinella-Vega; Roberto Carlos Ojeda-Gómez (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the antibacterial effect of electrolytically generated hypochlorous acid on Streptococcus gordonii, Fusobacterium nucleatum, and Porphyromonas gingivalis. Material and Methods: In this in vitro experiment, the effect of hypochlorous acid (HOCl) on the strains S. gordonii, F. nucleatum, and P. gingivalis was evaluated using 4% sodium hypochlorite, 0.12% chlorhexidine, and distilled water as controls. The four groups were placed on each plate, and each group was replicated five times. The agar diffusion method by zones measurement was used. The data were processed with SPSS using the Kruskal-Wallis test and multiple comparison tests. Results: Hypochlorous acid showed an average inhibition halo of 9.28 mm on S. gordonii. As expected with distilled water, no zone of inhibition was noted for any of the bacteria, nor were zones of inhibition observed with HOCl for F. nucleatum and P. gingivalis. Conclusion: Hypochlorous acid showed antimicrobial properties against only S. gordonii and was less effective than 4% sodium hypochlorite and 0.12% chlorhexidine, although no significant differences were found between the latter.